The Goblin spider genus Xestaspis in Sri Lanka (Araneae: Oonopidae) - Ranasinghe, U. G. S. L.; Benjamin, Suresh. P. (Zootaxa, 2016)
Three new species of the genus Xestaspis Simon, 1884: X. nuwaraeliya sp. nov., X. padaviya sp. nov. and X. pophami sp. nov. are described based on both sexes. Xestaspis kandy Eichenberger, 2012 is illustrated based on new material. A key and a distribution map for Sri Lankan Xestaspis is provided. Phylogenetic placement of Sri Lankan Xestaspis spp. obtained by the analysis of 43 morphological characters is presented and discussed. In all our analysis Gamasomorpha species appear paraphyletic suggesting that Xestaspis is most probably a junior synonym of Gamasomorpha. Thus, forming monophyletic group of oriental hard bodied oonopids.